Polyaniline Conducting Electroactive Polymers Thermal and Environmental Stability Studies - Reza Ansari; M. B. Keivani (E-Journal of Chemistry)
In the current studies, polyaniline (PANi) was prepared both chemical and electrochemically in the presence of different bronsted acids from aqueous solutions. The effect of thermal treatment on electrical conductivity, and thermal stability of the PANi conducting polymers were investigated using 4-point probe and TGA techniques respectively. It was found that polymer prepared by CV method is more thermally stable than those prepared by the other electrochemical techniques. In this paper we have also reviewed some fundamental information about synthesis, general properties, diverse applications, thermal and environmental stability of polyaniline conducting polymers.